Inovasi dan pertumbuhan: Kunci sukses pembangunan start-up dalam ekonomi modern - Firdaus, Violinda Syahgaria (Maliki Interdisciplinary Journal, 2024)
In the modern economy, innovation and growth are the cornerstones for start-up success. This article emphasizes how innovation plays an important role in supporting the competitiveness and growth of start-ups. Developing new products, utilizing technological advancements, and employing creative marketing strategies are some of the innovations that help start-ups increase market share and create added value. Start-ups can solve complex problems and improve their operational efficiency by leveraging technological innovations such as artificial intelligence (AI)-based solutions or blockchain-based applications. On the other hand, start-ups have to face challenges such as availability of resources, fierce competition, funding constraints, lack of innovation, inconsistency, and risk of failure. Addressing these issues is critical to the success of a start-up.